2013
DOI: 10.5847/wjem.j.issn.1920-8642.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ulinastatin on paraquat-induced-oxidative stress in human type II alveolar epithelial cells

Abstract: BACKGROUND:Ulinastatin (UTI) is a urinary trypsin inhibitor extracted and purified from urine of males. This study aimed to explore the effects of UTI on paraquat-induced-oxidative stress in human type II alveolar epithelial cells.METHODS:The human type II alveolar epithelial cells, A549 cells, were cultured in vitro. The A549 cells were treated with different concentrations of paraquat (200, 400, 600, 800, 1 000, 1 200 µmol/L) and ulinastatin(0, 2 000, 4 000, 6 000, 8 000 U/mL) for 24 hours, the cell viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Exposure to environmental hazards including herbicides is one of the challenges that faces the scientists to discover and measure the safety of human health especially in occupational exposure that affect the people medical social and economic sides. Oxidative stress and radicals has been recorded to be the major mechanism causing paraquat (PQ) toxicity [41].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to environmental hazards including herbicides is one of the challenges that faces the scientists to discover and measure the safety of human health especially in occupational exposure that affect the people medical social and economic sides. Oxidative stress and radicals has been recorded to be the major mechanism causing paraquat (PQ) toxicity [41].…”
Section: Discussionmentioning
confidence: 99%
“…The determination of SOD and MDA could refl ect the ability of scavenging oxygen free radicals and the anti-lipid peroxidation damage, respectively. [7] Studies [5,6] have reported that PQ might exert its cytotoxicity through mitochondrial dysfunction. Mitochondrial dysfunction is one of the manifestations that free radicals attack the body.…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest research survey, 80% of white-collar workers in China are in the state of overfatigue at present. About 95.7% of young people have died of fatigue-related fatal diseases [1]. According to statistics, the annual incidence of sudden death in Western European and American countries is 0.1-0.2%.…”
Section: Epidemiologymentioning
confidence: 99%
“…Haiyan Zhu 1,2 *, Guoxin Han 3 and Shuoshuo Li 1 1 Emergency Department, The First Medical Center of Chinese PLA General Hospital, Beijing, China…”
Section: Author Detailsmentioning
confidence: 99%